ENHANCING THE COMPETITIVENESS OF DOMESTIC ENTERPRISES IN THE CONTEXT OF EUROPEAN INTEGRATION - HRYTSYNA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the directions for enhancing the competitiveness of domestic enterprises within the context of European integration processes and growing global challenges. It substantiates that increasing competition in both domestic and foreign markets requires enterprises to adopt a comprehensive approach to strengthening their market positions. This approach encompasses innovative development, digital transformation, production modernization, effective logistics strategy, and the formation of a highly qualified workforce.Particular attention is paid to the role of digitalization as a key factor in boosting competitive advantages, integrating modern technologies into business models, and implementing ERP and SCM systems, artificial intelligence, the Internet of Things, and big data analytics. It is argued that digitalization serves as a strategic tool for business entities to adapt to market dynamics, enabling the rationalization of resource management, improvement of product and service quality, and the generation of innovative business models.The study highlights the significance of human capital as a strategic resource for enterprises.  Achieving the required level of personnel competitiveness is determined by the systematic development of knowledge, skills, and abilities, combined with fostering a favorable socio-psychological climate and appropriate organizational conditions. The importance of adaptive strategies for ensuring competitiveness under martial law is emphasized, including activity diversification, energy efficiency, risk management, and utilization of state support programs.It is noted that managing an enterprise's competitiveness should be oriented towards ensuring its viability and stable operation, irrespective of changes in the external environment caused by economic, political, or social factors. Accordingly, managerial influence should include neutralizing or minimizing negative factors through the formation of appropriate protective mechanisms, leveraging favorable external conditions to enhance and realize competitive advantages, and ensuring the adaptability of management decisions by aligning them with the dynamics of both positive and negative determinants of market competition.The study concludes that sustainable competitiveness is achievable only through the comprehensive adaptation of enterprises to European integration requirements, innovative development, and strategic risk management.
Keywords: competitiveness; European integration; digitalization; human capital; logistics activity; adaptation; martial law